Prestasi Belajar Akademik pada Mahasiswa : Bagaimana peranan manajemen waktu? - Claudia Nungki Santoso Putri; Amherstia Pasca Rina; IGAA Noviekayati (INNER: Journal of Psychological Research, 2023)
Abstract Indonesian educational institutions have not changed. This event can be seen from the decline in the ability of students in Indonesia which is still the same and there are no more positive changes. The learning process is one of the factors that can affect learning outcomes. The purpose of this study was to determine the relationship between time management and student achievement. The subjects in this study were 54 students who already had a GPA. The data collection tool used is the time management scale Atkinson’s theory (1994). The reliability study was assisted by the SPSS for Windows Release version 25.00 computer program with the Fisher exact test. The results of the reliability test on the time management scale showed a Cronbach Alpha of 0.926. Based on these results, the Cronbach Alpha value is close to 1.00, which means that the reliability of the time management scale with 40 items after 2 rounds of analysis is classified as very high. Then it is known that the Chi-square test obtained a value of p = 0.000 (p <0.001) so that it can be interpreted that there is a positive relationship between time management and student achievement. Keywords: Time Management, Learning Achievement